Optimizing Digital Applications To Enhance Operational Efficiency In MSMEs And Accelerate The Digital Economy - Septiano, Renil; WP, Dwi Atmodjo; Fauzi, Maulidza Nur; Suratman, Suratman; Chatra, Afdhal (SEAN Institute, 2024)
Improving the operational efficiency of MSMEs and quickening the digital economy depend on optimizing digital apps in the fast changing digital environment. Many MSMEs, meanwhile, struggle with things like low technical skills, limited funds, and opposition to change. This paper investigates how digital apps could help MSMEs overcome obstacles and suggests efficient ways to maximize the usage of digital technology by means of the literature review approach. Digital apps include data analytics, digital marketing, and inventory control can help MSMEs become more competitive, more efficient, and productive, according the literature study. Case studies from Indonesia, such the UMKM Go Digital initiative, highlight the good effects of digital technology acceptance. The outcomes highlight the need of government and corporate sector cooperation in offering the required skills, resources, and infrastructure to assist the digitization of MSMEs. With the correct approach, digital technology may be a main engine of equitable and sustainable economic development.